Islamic Economic Thought: A Flashback Of Their Characters And Thoughts - Dian Zahra Syahfitri Lubis; Fathiya Syahidah Nasution; Mutia Salwa Hutauruk; Ahmad Wahyudi Zein (Sean Institute, 2024)
Islamic economic thought has developed from classical to modern times, making significant contributions to creating an economic system based on justice, balance, and sustainability. This study aims to examine the ideas of Islamic economic figures, such as Al-Ghazali, Ibn Khaldun, Muhammad Baqir al-Sadr, and Abul A'la Maududi , who offers solutions to various economic challenges, both in their time and in the contemporary era. The research method used is library research, by collecting data from various primary and secondary sources, including books, journals, and relevant scientific articles. The results of the study show that these figures have complementary views, where classical thought emphasizes basic principles such as justice and morality in economics, while modern figures offer applicable concepts such as zakat management, prohibition of usury, and the sharia financial system as a solution to social inequality and economic exploitation. This study confirms that Islamic economic thought is not only oriented towards material gain, but also spiritual and social balance, making it a relevant and sustainable alternative in responding to global economic challenges.